Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening Pada CV. Kedai Kreasi Digital di Yogyakarta - Rita Ayu Wijayanti (Universitas Mercu Buana, 2020)
This study aims to analyze the influence of the work environment and work discipline on employee performance with job satisfaction as an intervening variable on the CV. Kedai Kreasi Digital in Yogyakarta. The variables used in this study are the work environment, work discipline, job satisfaction, and employee performance. The population in this study were all employees of CV. Kedai Kreasi Digital in Yogyakarta, amounting to 60 employees. The method used in sampling is the census, which is a sampling technique by taking the entire population, so that the total sample of this study is 60 employees. Data analysis methods include Descriptive Analysis and Path Analysis using SPSS for Windows version 23. The results of the study indicate that 1) The work environment has a positive and significant effect on employee performance. 2) Work discipline has a positive and significant effect on employee performance. 3) The work environment has a positive and not significant effect on employee performance with job satisfaction as an intervening variable. 4) Work discipline has a positive and significant effect on employee performance with job satisfaction as an intervening variable.